ANALISA PERLINDUNGAN KESEJAHTERAAN BURUH MENURUT HUKUM EKONOMI SYARI’AH - Kevin al Sidiq; Misno (JURNAL ALAMIAH, 2022)
Welfare is the right of every citizen according to the fifth precept of "social justice for all the people of Indonesia" should the nation of Indonesia get the welfare equally for all circles without exception. Workforce work in order to meet the needs and prosperity of his family is appropriate the state participate in protecting their rights as citizens of Indonesia are listed in Law No. 13 of 2003 on employment. Shari'ah economics also regulates relating to the welfare of the workforce This study uses a comparative descriptive method of legal studies (comparative legal study) with a qualitative approach, namely comparing the protection of laborers 'welfare in the law number 13 of 2003 on employment with workers' welfare in the concept of shari'ah economy.